Factorial validity, measurement equivalence and cognitive performance of the Cambridge Neuropsychological Test Automated Battery (CANTAB) between patients with first-episode psychosis and healthy volunteers - Haring, L.; Mõttus, R.; Koch, K.; Trei, M.; Maron, E. (Psychological medicine, 2015)
The purpose of this study was to use selected Cambridge Neuropsychological Test Automated Battery (CANTAB) tests to examine the dimensional structure of cognitive dysfunction in first episode of psychosis (FEP) patients compared with cognition in healthy subjects. A total of 109 FEP patients and 96 healthy volunteers were administered eight CANTAB tests of cognitive function. Principal components analysis (PCA) was used to estimate dimensionality within the test results. The dimensions identified by the PCA were assumed to reflect underlying cognitive traits. The plausibility of latent factor models was estimated using confirmatory factor analysis (CFA). Multi-group CFA (MGCFA) was used to test for measurement invariance of factors between groups. The nature and severity of cognitive deficits amongst patients as opposed to controls were evaluated using a general linear model. Amongst subjects PCA identified two underlying cognitive traits: (i) a broad cognitive domain; (ii) attention/memory and executive function domains. Corresponding CFA models were built that fitted data well for both FEP patients and healthy volunteers. As in MGCFA latent variables appeared differently defined in patient and control groups, differences had to be ascribed using subtest scores rather than their aggregates. At subtest score level the patients performed significantly worse than healthy subjects in all comparisons (p < 0.001). Results of this study demonstrate that the structure of underlying cognitive abilities as measured by a selection of CANTAB tests is not the same for healthy individuals and FEP patients, with patients displaying widespread cognitive impairment.